Disruption to TFEB signaling and autophagy in newly formed oligodendrocytes leads to aberrant generation of CNS myelin - Daniela Barbosa; Aksheev Bhambri; Miguel Vasquez; Yihe Zhang; Gabrielle Sanchez; Katherine J. Wert; Natalia V Gounko; Mark H. Ellisman; Lu O. Sun (Proceedings of the National Academy of Sciences, 2026)
Myelin is a defining feature of the vertebrate nervous system, yet the cellular and molecular mechanisms governing its integrity remain poorly understood. Here, using volume electron microscopy and a knock-in mouse line targeting newly formed oligodendrocytes, we reconstruct early optic nerve myelination and examine retinal ganglion cell axon ensheathment. We observe that newly formed myelin sheaths exhibit membrane protrusions and occasional degenerative myelin “whorls.” Conditional disruption of the transcription factor EB (TFEB)-autophagy pathway in newly formed oligodendrocytes significantly increases the abundance of these aberrant myelin structures, indicating that this pathway is required for proper myelin formation and integrity. Importantly, this pathway acts independently of the well-established function of TFEB that represses myelin sheath growth. Together, our findings identify a role for TFEB-dependent autophagy in establishing proper myelin structure during development, providing insights into the oligodendrocyte-intrinsic mechanisms that regulate myelin integrity.